2020
DOI: 10.2147/dmso.s252971
|View full text |Cite
|
Sign up to set email alerts
|

<p>Increased Energy Expenditure and Energy Loss Through Feces Contribute to the Long-Term Outcome of Roux-en-Y Gastric Bypass in a Diet-Induced Obese Mouse Model</p>

Abstract: Background: Roux-en-Y gastric bypass (RYGB) has been proved to be more effective than other bariatric procedures in the long term on bodyweight loss and remission of diabetes. However, the mechanism remains poorly understood. Long-term changes in energy metabolism after RYGB have rarely been reported. Objective: To investigate the long-term effects of RYGB on energy metabolism on a dietinduced obesity (DIO) mouse model. Methods: DIO mice fed a high-fat diet were assigned to two groups: RYGB (n=8) and sham (n=7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…2g). Furthermore, our previous study 28 indicated that the daily food intake of mice in the RYGB group was not different from that of mice in the sham group. Hence, the amount of food intake is not a confounding factor for the improved gut permeability in the RYGB model.…”
Section: Discussionmentioning
confidence: 85%
“…2g). Furthermore, our previous study 28 indicated that the daily food intake of mice in the RYGB group was not different from that of mice in the sham group. Hence, the amount of food intake is not a confounding factor for the improved gut permeability in the RYGB model.…”
Section: Discussionmentioning
confidence: 85%